2016
DOI: 10.1053/j.gastro.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Crypt Genesis and Development of Familial Small Intestinal Neuroendocrine Tumors

Abstract: Background & Aims Small intestinal neuroendocrine tumors (SI-NET) are serotonin-secreting well-differentiated neuroendocrine tumors believed to originate from enterochromaffin (EC) cells. Intestinal stem cell (ISC) are believed to contribute to formation of SI-NET, although little is known about tumor formation or development. We investigated the relationship between EC cells, ISCs, and SI-NETs. Methods We analyzed jejuno-ileal tissue specimens from 14 patients with familial SI-NETs enrolled in the Natural H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…The cells we identify with high expression of Bmi1 , EE-restricted TFs, and gut hormones may represent the murine equivalent of crypt cells that give rise to carcinoid tumors. This idea matches with evidence that human carcinoid tumors arise in cells with BMI1 levels modestly higher than in surrounding crypt cells (Sei et al, 2016). …”
Section: Discussionsupporting
confidence: 88%
“…The cells we identify with high expression of Bmi1 , EE-restricted TFs, and gut hormones may represent the murine equivalent of crypt cells that give rise to carcinoid tumors. This idea matches with evidence that human carcinoid tumors arise in cells with BMI1 levels modestly higher than in surrounding crypt cells (Sei et al, 2016). …”
Section: Discussionsupporting
confidence: 88%
“…3B). Previous studies have suggested that SINETs originate from CgA-positive cells in the epithelium at the base of the intestinal crypts (15). We thus also quanti ed the number of CgA-positive cells located speci cally at the bottom of the intestinal crypts (up to and including position + 4), but did again not observe any signi cant difference between the two genotypes (Fig.…”
Section: Heterozygous Inactivation Of Smad4 Is Not Su Cient To Inducementioning
confidence: 76%
“…The presence of LGR5 ‐positive cell in neuroendocrine neoplasms may suggest that these neoplasms have the same stem cells originating from adenoma and carcinoma in the colorectum. The presence of cells that are positive for both LGR5 and synaptophysin in NEC may be related to acquisition of neuroendocrine features at an early stage of intestinal differentiation . Although there is no evidence that NET G1 and NET G2 are etiologically related to adenoma and adenocarcinoma, one report suggested that LGR5 may be a NET stem cell marker in the small intestine .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of cells that are positive for both LGR5 and synaptophysin in NEC may be related to acquisition of neuroendocrine features at an early stage of intestinal differentiation. 19 Although there is no evidence that NET G1 and NET G2 are etiologically related to adenoma and adenocarcinoma, one report suggested that LGR5 may be a NET stem cell marker in the small intestine. 19 The authors demonstrated the double positive cells for LGR5 and a neuroendocrine marker in NET, suggesting the possibility that LGR5 is stem cell marker in NET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation